2015
DOI: 10.1128/iai.01064-15
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Amylase Is an Environmental Signal for Regulation of Biofilm Formation and Host Interaction in Campylobacter jejuni

Abstract: f Campylobacter jejuni is a commensal bacterium in the intestines of animals and birds and a major cause of food-borne gastroenteritis in humans worldwide. Here we show that exposure to pancreatic amylase leads to secretion of an ␣-dextran by C. jejuni and that a secreted protease, Cj0511, is required. Exposure of C. jejuni to pancreatic amylase promotes biofilm formation in vitro, increases interaction with human epithelial cell lines, increases virulence in the Galleria mellonella infection model, and promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…jejuni and inactivation of each has been linked to the attenuation of C . jejuni physiology, virulence, and/or immunogenicity (Brondsted et al, ; Jowiya et al, ; Karlyshev et al, ). The enhanced proteolytic activity of 11168H ST‐OMVs indirectly indicates a more pathogenic C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…jejuni and inactivation of each has been linked to the attenuation of C . jejuni physiology, virulence, and/or immunogenicity (Brondsted et al, ; Jowiya et al, ; Karlyshev et al, ). The enhanced proteolytic activity of 11168H ST‐OMVs indirectly indicates a more pathogenic C .…”
Section: Discussionmentioning
confidence: 99%
“…*, p < .05. ST = sodium taurocholate; PBS = phosphate buffered saline; OMVs = outer membrane vesicles linked to the attenuation of C. jejuni physiology, virulence, and/or immunogenicity(Brondsted et al, 2005;Jowiya et al, 2015;Karlyshev et al, 2014). The enhanced proteolytic activity of 11168H ST-OMVs indirectly indicates a more pathogenic C. jejuni response during colonisation of a host after the bacteria senses bile salts.…”
mentioning
confidence: 99%
“…Host signals also play a role; a recent study showed that C. jejuni 11168 can produce a glucan biofilm composed of α-dextran as a specific response to the presence of host pancreatic amylase (Jowiya et al, 2015). In contrast to the clear stimulatory effect of glucose on biofilm formation we found here, the only other sugar known to be metabolized by campylobacters, L -fucose, was very recently shown to reduce biofilm formation in the C. jejuni NCTC 11168 strain (Dwivedi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although the formation of C . jejuni biofilms is not fully understood, as with many other bacteria they contain DNA [ 7 , 12 ] and polysaccharide [ 13 ].…”
Section: Introductionmentioning
confidence: 99%